Study on the optimization of mercury ion (II) adsorption with activated carbon from a biomass combination of palm bunches and rice husk - Suhendrayatna Suhendrayatna; Abdurrahman Abdurrahman; Elvitriana Elvitriana (Graduate Program of Syiah Kuala University, 2019)
This research deals with the adsorption of mercury ions [Hg (II)] using a combination of natural biomass between oil palm bunches and rice husks (PB-RH). After drying at 40oC, PB-RH biomass was carbonized by using a tube furnace for 2 hours at 500 °C and followed chemical activation with citric acid. Activated carbon formed was contacted with an aqueous solution containing Hg (II) ion and stirred at a constant rate of 150 rpm. The concentration of Hg (II) ions in the aqueous phase were analyzed with Atomic Absorption Spectrophotometer (AAS) and the Central Composite Design (CCD) method with Design-Expert software version 6.0.8 was conducted to calculate the optimization of adsorption capacity for mercury ion. The Hg ion adsorption capacity was estimated to observe the performance of the PB-RH biomass combination on the adsorption of Hg (II) ions with some variables, such as contact time, biomass weight, and activator concentration. Results showed that all variable response, contact time, biomass weight, and activator concentration influenced the mercury (II) ion adsorption capacity. The optimum condition of Hg (II) ion adsorption occurred at 30 g of activated PB-RH biomass with 0.6 mole/L concentration of activator during 99.88 minutes with 99.42 mg/L initial concentration of Hg (II). The adsorption capacity occurred at 10.1 mg/g as the optimum condition for the adsorption of Hg (II) ions by PB-RH.